Atrakcyjność inwestycyjna województwa kujawsko-pomorskiego w świetle członkostwa Polski w Unii Europejskiej (Świat Idei i Polityki, 2010)
Despite the progressing outer convergence of Poland, it can be stated that, with the exception of a few big cities and few areas attractive in terms of tourism and agriculture, all Polish voivodships are threatened by the peripheralization in the integrating Europe. Furthermore, the restructurization processes of industry and agriculture together with a slow privatization of these branches of economy, despite visible positive results, brought about threats of unemployment, a low investment ability, little competitiveness of enterprises or ineffectiveness of the institutional system. What is more, the above-mentioned dangers occur to different degrees in different regions. Therefore, a low socio-economic cohesion is itself an obstacle to the enlargement of the cohesion at the European level. This paper tries to present the current level of socio-economic development of Polish voivodships, especially Kujawsko-Pomorskie, within the context of cohesion policy of the European Union.